The effects of iTBS to cerebellar vermis on balance function in frail older people: A protocol for a randomized controlled trial - Zuoyan Liu; Neng Huang; Kehong Zhao; Na Long; Ruibao Fu; Xiuying Hu (PLoS ONE, 2026)
Background With the gradual deepening of the aging of the population, the closely related problem of frailty in older people is becoming increasingly prominent. Frailty can increase the risk of bodily damage and adverse health outcomes such as falls, disabilities, hospitalizations, institutionalization, and death. Intermittent theta burst stimulation is a special stimulation mode of repetitive transcranial magnetic stimulation, which can enhance synaptic transmission by mimicking cortical theta rhythms. Some previous studies have suggested that intermittent theta burst stimulation is effective in improving balance function and motor function. However, few studies have explored the effects of intermittent theta burst stimulation to cerebellar vermis on balance function in frail older people. Objective To introduce a randomized controlled trial protocol, which will be used to evaluate the efficacy of intermittent theta burst stimulation to cerebellar vermis on balance function in frail older people. Methods This trial is a double-blind, two-arm randomized controlled trial. Frail older people with balance dysfunction will be recruited. All participants will be randomly assigned to experimental group who will receive intermittent theta burst stimulation to cerebellar vermis and control group who will receive false stimulation in a 1:1 ratio. All participants will also receive motor training once a day for 30–60 minutes each time, for a total of 20 sessions. The primary outcome will be balance function and the secondary outcomes will include frailty, walking ability, sensory organisation test, limits of stability, and rhythmic weight shift. All outcomes will be collected at baseline and in the week immediately post-intervention. Discussion This study will be the first randomized controlled trial on the effects of iTBS to cerebellar vermis on balance function in frail older people. It is expected that this study, if proven effective in improving the balance function in frail older people, will provide evidence-based rehabilitation strategies for rehabilitation therapist. Trial status Screening of participants will begin in September 2025.